2022
DOI: 10.3390/vaccines10091394
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative RT-PCR Assays for Quantification of Undesirable Mutants in the Novel Type 2 Oral Poliovirus Vaccine

Abstract: Emergence of mutations is an inherent property of RNA viruses with several implications for their replication, pathogenesis, and evolutionary adaptation. Oral poliovirus vaccine (OPV), developed by Albert Sabin, is composed of live attenuated polioviruses of three serotypes that can revert to neurovirulence during replication in cell culture and in vaccine recipients. Recently, a new modified variant of Sabin 2 virus was developed by introducing changes in its genome, making it more genetically stable to preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…But, in the case of nOPV2 vaccines, the E 295 K mutation causes loss of antigenicity/immunogenicity [16] . The E 295 K mutation is currently biologically best characterized for nOPV2 vaccines [22] , [26] and thus closely monitored during manufacturing processes using costly and time-consuming NGS analysis. The here-developed AS LNA qPCR assay correlates well with NGS data regarding E 295 K detection and quantification and may present a low-cost, high-throughput pre-screening alternative to NGS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But, in the case of nOPV2 vaccines, the E 295 K mutation causes loss of antigenicity/immunogenicity [16] . The E 295 K mutation is currently biologically best characterized for nOPV2 vaccines [22] , [26] and thus closely monitored during manufacturing processes using costly and time-consuming NGS analysis. The here-developed AS LNA qPCR assay correlates well with NGS data regarding E 295 K detection and quantification and may present a low-cost, high-throughput pre-screening alternative to NGS.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the position of the mutations of interest, either short-read or long-read sequencing will be needed to determine if mutations are co-locating. Manukyan et al recently published a quantitative multiplex, one-step RT-PCR for assessing selected neurovirulence mutations and the E 295 K mutation [22] . Though a direct comparison between accuracy, specificity, and sensitivity results is not feasible due to the different materials used, our AS LNA-based technology, has major advantages over the Manukyan-approach: The presented LNA incorporation in the probes leads to higher annealing temperatures (Tms) of probes, allowing for shorter probe lengths with better quenching and a higher signal-to-noise ratio and thus an improved ability to distinguish SNPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that poliovirus targets the motor neurons in the spinal cord, and causes damage to motor neurons leading to paralysis. The most effective polio vaccine functions at the entry level of viral infection systematically, specially the digestive system (23, 24).…”
Section: Viral Pathogenicitymentioning
confidence: 99%
“…Can we retrospectively have a systems vaccinology mindset to learn from the effective polio vaccines? Specifically, it has been reported that a vaccine variant has caused a recent polio epidemic (23,24).…”
Section: Approaches To Prevent the Next Pandemicmentioning
confidence: 99%